Novel phenylalanine derived diamides as Factor XIa inhibitors. Issue 2 (15th January 2016) - Smith, Leon M.; Orwat, Michael J.; Hu, Zilun; Han, Wei; Wang, Cailan; Rossi, Karen A.; Gilligan, Paul J.; Pabbisetty, Kumar B.; Osuna, Honey; Corte, James R.; Rendina, Alan R.; Luettgen, Joseph M.; et al.
Graphical abstract: Abstract: The synthesis, structural activity relationships (SAR), and selectivity profile of a potent series of phenylalanine diamide FXIa inhibitors will be discussed. Exploration of P1 prime and P2 prime groups led to the discovery of compounds with high FXIa affinity, good potency in our clotting assay (aPPT), and high selectivity against a panel of relevant serine proteases as exemplified by compound21 . Compound21 demonstrated good in vivo efficacy (EC50 = 2.8 μM) in the rabbit electrically induced carotid arterial thrombosis model (ECAT).